Assessment of event-related evoked potentials and China-Wechsler intelligence scale for cognitive dysfunction in children with obstructive sleep apnea. (November 2021) - Shi, Yewen; Feng, Yani; Zhang, Yitong; Liu, Haiqin; Luo, Huanan; Shang, Lei; Xing, Liang; Hou, Jin; Yan, Jing; Liu, Xiaohong; Zhang, Qingqing; Si, Chao; et al.
Abstract: Objective: To explore the relationship between obstructive sleep apnea (OSA) and cognitive impairment by combining event-related evoked potentials (ERPs) and China-Wechsler Younger Children Scale (C-WISC) in children with sleep-disordered breathing (SDB) with vs. without OSA. Methods: This was a retrospective case-control study of all consecutive children (n = 148) with adenoid tonsil hypertrophy between July 2017 and March 2019 at the Hospital. Results: The children were divided into the OSA (n = 102) and non-OSA (n = 46) groups. The apnea-hypopnea index (AHI), obstructive apnea index (OAI), and obstructive apnea-hypopnea index (OAHI) in the OSA group were elevated compared with those of the non-OSA group (all P < 0.001). The mean oxygen saturation (SaO2 ) and SaO2 nadir were lower in the OSA group compared with the non-OSA group (both P < 0.001). The respiratory arousal index (RAI) values in the OSA group were larger than those of the non-OSA group (P < 0.001). The P300 and N100 latencies in the OSA group were longer than those of the non-OSA group (both P < 0.001). Pearson's correlation analysis revealed correlations of the P300 peak latency with full-scale intelligence quotient (FIQ) (P < 0.001 and r = −0.527), verbal intelligence quotient (VIQ) (P < 0.001 and r = −0.448), and performance intelligence quotient (PIQ) (P < 0.001 and r = −0.515). There was a correlation between the N100 peak latency and PIQ (P = 0.026 and r = −0.183). Conclusion: ERPs, as an objective measurement, might help assess cognitive impairment in children with OSA.